Sustainability in executive remuneration : A missing link towards more sustainable firms? - Hartikainen, Heta; Järvenpää, Marko; Rautiainen, Antti (Elsevier, 2021)
This paper contributes by showing simultaneously the interlinked challenges of sustainability-based (based on long-term economic, social and environmental targets) executive remuneration and the problems of transparency in remuneration reporting. Our empirical data, analyzed using qualitative content analysis, consists of the published remuneration statements and sustainability reports of 43 Finnish companies reporting according to the Global Reporting Initiative (GRI) framework. Our results indicate that comprehensive sustainability remuneration is still rare in Finnish large companies: long-term financial targets are implemented at most companies, but social or environmental targets were only reported by 7 companies (16%). We conclude that executive remuneration policies are still mainly concerned with financial targets and aligning the interests of executives and shareholders and ignoring other stakeholders. The dominance of the remuneration reporting by the local Finnish Corporate Governance Code (FCGC) over GRI reporting on remuneration highlights sustainability accounting as local practice and is a reason for the lack of fully transparent reporting about the criteria of sustainability remuneration. We conclude that sustainable executive remuneration and simultaneously lacking transparency of reporting on it do not support implementation of sustainability strategies in Finnish companies and may hinder the development towards genuine sustainability and shows that there is an important (missing) link between incentives and sustainability in business.
Keywords: Sustainability; Remuneration; Transparency; Reporting; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|